A Comparison of Sexual Minority and Heterosexual College Students on Gendered Sexual Scripts and Sexual Coercion Perpetration. Issue 7 (April 2023) - Fournier, Lauren F.; Pathak, Neha; Hoffmann, Amy M.; Verona, Edelyn
Prior work has identified endorsement of gendered sexual script beliefs as predictive of sexual coercion perpetration among heterosexual individuals, primarily men. This research is lacking among sexual minority individuals and may be important in informing inclusive and effective sexual coercion prevention efforts. The current study sought to (1) assess the level of adherence to gendered sexual script beliefs, (2) report relative rates of general sexual coercion and sexual intimate partner violence (IPV), and (3) examine the relationship between gendered sexual script beliefs and self-reported sexually coercive behavior among sexual minority and heterosexual college men and women. Undergraduate students ( n  = 1, 199; 182 sexual minorities) completed self-report measures assessing gendered sexual script beliefs, sexual coercion perpetration, and sexual IPV. Results from Gender × Sexual Minority group ANOVAs and logistic regression analyses indicated similar rates of perpetration across sexual orientation groups, with men overall reporting the most perpetration. Furthermore, men and heterosexual individuals adhered more strongly to gendered sexual scripts than women and sexual minority individuals, respectively. Results of path models revealed no moderation by sexual orientation, and that adherence to gendered sexual scripts was positively related to sexual IPV perpetration among the full sample of heterosexual and nonheterosexual individuals, though this effect was small. Gendered sexual scripts did not significantly relate to general sexual coercion perpetration among the full sample, suggesting that traditional sexual script beliefs may not be as relevant to perpetration in a contemporary college sample. This study adds to limited literature on sexual coercion perpetration among sexual minority individuals and is an important step in understanding relationships between endorsement of gendered sexual script beliefs and sexual coercion perpetration among sexual minority and heterosexual college students.